Nikodim P. Kondakov and Mikhail I. Rostovtzev: A Teacher and his Disciple - Kashcheev, Vladimir (Hyperboreus, 2021)
The inﬂuence of the outstanding scholar N. P. Kondakov and his research school on M. I. Rostovtzev as a scholar was multifaceted and powerful. The main lines of this inﬂuence are traced here: the young Rostovtzev’s attendance of his teacher’s lectures on art history and archaeology at the university, his participation in the circle established by Kondakov at the Museum of Antiquities, their joint research trips, especially to Italy and Spain in 1896, Rostovtzev’s visits to the jours ﬁxes in Kondakov’s home (the so-called Liberal Academy), his personal meetings and talks with Kondakov and Kondakov’s pupils, especially with Ya. I. Smirnov and S. A. Zhebelev, and his study of Kondakov’s scholarly works. M. I. Rostovtzev took a new approach to the animal style, which his teacher had researched for many decades. Kondakov’s idea that “mixing one’s own (local) forms and the forms of another people leads to the creation of something new” in culture and art was developed in detail by Rostovtzev using the example of Scythia and the Bosporus. This essay shows that the idea of progress in its pure form, which was relevant to the humanities and social sciences of the late nineteenth and early twentieth centuries, was alien to both teacher and disciple. Having passed through Kondakov’s school, M. I. Rostovtzev had completely mastered its characteristic method and was able to conduct a stylistic analysis of the most diverse works of art. However, he did not become an art historian, perhaps because he had another teacher, the celebrated philologist F. F. Zelinsky, thanks to whom, as a researcher, he was able to proﬁt from the life-giving source of classical philology. N. P. Kondakov was ﬁrst and foremost an art historian and a Byzantinist, but also an archaeologist. For his part, M. I. Rostovtzev can rightfully be considered an archaeologist, all the more so because he directed the excavations at Dura-Europos in 1928–1937. However, archaeology was not the main focus of his scholarly interests. He was one of the very rare universal scholars of antiquity in this era who was capable of working professionally in many branches of classical studies. Most of all, he was an ancient historian who was able to view the history of the ancient world as a kind of union of politics, economics, social relations, religion, culture and everyday life. M. I. Rostovtzev, as well as his prominent teachers N. P. Kondakov and F. F. Zelinsky, belongs to the classical tradition associated with St Petersburg.